2020
DOI: 10.3788/col202018.062403
|View full text |Cite
|
Sign up to set email alerts
|

Morse lens [Invited]

Abstract: In this Letter, we find that Morse potential (proposed about 90 years ago) could be connected to Coulomb potential (or Newton potential) and harmonic potential (or Hooke potential) by conformal mappings. We thereby design a new conformal lens from Morse potential, Eaton lens, and Luneburg lens and propose a series of generalized Eaton/Luneburg lenses. We find that this Morse lens is a perfect self-focusing asymmetric lens that differs from a Mikaelian lens. Our theory provides a new insight to Morse potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The Mikaelian lens (independently proposed in 1951) is a conformal-mapping lens derived from Maxwell's fish-eye lens and qualifies as an AI [24,25]. Chen et al introduced the Morse lens based on the Morse potential, serving as a valuable augmentation to one-dimensional (1D) AIs [26]. Because of the periodic and closed orbit characteristics of light rays in AIs, Tyc et al performed a frequency analysis and discovered that the frequency spectra are spaced almost equally [27,28], and then concluded that the AIs are actually good superintegrability systems [29].…”
Section: Introductionmentioning
confidence: 99%
“…The Mikaelian lens (independently proposed in 1951) is a conformal-mapping lens derived from Maxwell's fish-eye lens and qualifies as an AI [24,25]. Chen et al introduced the Morse lens based on the Morse potential, serving as a valuable augmentation to one-dimensional (1D) AIs [26]. Because of the periodic and closed orbit characteristics of light rays in AIs, Tyc et al performed a frequency analysis and discovered that the frequency spectra are spaced almost equally [27,28], and then concluded that the AIs are actually good superintegrability systems [29].…”
Section: Introductionmentioning
confidence: 99%
“…Drawing upon the form invariance of Maxwell's equations under coordinate transformation, transformation optics (TO) theory [18][19][20] can arbitrarily regulate electromagnetic field based on specific demands, providing many novel devices such as invisibility cloaks [21], field rotators [22], illusion devices [23], to name a few. Furthermore, due to the connection between virtual space and physical space, TO brings another insight to understand and design novel geometrically perfect lenses with gradient index [24]. If the coordinate transformation is extended to the imaginary/complex space coordinate domain [25], TO can help to facilitate the comprehension and construction of hyperbolic geometries, serving as a powerful tool for manipulating hyperbolic waves at nanoscale and polaritons.…”
Section: Introductionmentioning
confidence: 99%
“…These lenses not only have the characteristics of perfect imaging or self-imaging, their trajectories are simple circles or ellipses as well. Recently, one dimensional profile (gradient direction is just along x-axis) called Morse lens and two dimensional profile (gradient directions are along x-and y-axis) called generalized Eaton/Luneburg lenses have been discovered, with the refractive index n(x) = √ 2e −ax − e −2ax and n(r) = √ 2 r (a+2) − 1 r (2a+2) respectively, where Eaton lens (a = −1) and Luneburg lens (a = −2) are revealed to their two examples [10]. We can choose different rational number 'a' to realize lenses with different functions.…”
Section: Introductionmentioning
confidence: 99%